Joinability of Particulate Reinforced Alumix 231 Based Composite Materials Produced by Powder Metallurgy Route - Ates, H.; Gokmen, U.; Cinici, H.; Uzun, A.; Karakoc, H.; Turker, M. (Металлофизика и новейшие технологии, 2014)
In the present study, weldability of Alumix 231 based composite materials reinforced with Al₂O₃ and B₄C and produced by powder metallurgy route is investigated. Various amounts of (0, 5, 10, and 15% wt.)Al₂O₃ and B₄C powders are added to the pre-alloyed Alumix 231 (Al—2.5% Cu—0.5% Mg—14% Si) powders separately and then mixed in a three-dimensional mixer for 45 min. Powders are compacted and sintered in an argon atmosphere at 640°C for 4 h. Produced blocks are welded by the Tungsten Inert Gas (TIG) welding at 25 V, 197 A and 14 l/min shielded gas flow in commercially pure argon atmosphere. Macro- and microexamination together with some mechanical properties of the welded area are studied. The results show that, although high amount of particles resulted in a decrease in the density, these composite materials can still be welded by the TIG welding method successfully. Исследуется свариваемость произведённых методом порошковой металлургии композитных материалов на основе Alumix 231, армированных Al₂O₃ и B₄C. Различные количества (0, 5, 10 и 15 масс.%) порошков Al₂O₃ и B₄C по отдельности добавлялись в предварительно сплавленные порошки Alumix 231 (Al—2,5% Cu—0,5% Mg—14% Si), а затем перемешивались в трёхмерном миксере в течение 45 минут. Затем порошки прессовались и спекались в атмосфере аргона при 640°C в течение 4 часов. Полученные блоки сваривались вольфрамовой сваркой в атмосфере инертного газа при 25 В, 197 А и потоке инертного газа в 14 л/мин в атмосфере технически чистого аргона. Были проведены макро- и микроисследования некоторых механических свойств сварной зоны. Их результаты показали, что, хотя оказалось большое количество частиц с пониженной плотностью, эти композитные материалы могут быть успешно сварены методом вольфрамовой сварки в атмосфере инертного газа. Досліджується зварюваність вироблених методою порошкової металургії композитних матеріялів на основі Alumix 231, армованих Al₂O₃ і B₄C. Різні кількості (0, 5, 10 і 15 мас.% ) порошків Al₂O₃ і B₄C окремо додавалися у попередньо стоплені порошки Alumix 231 (Al—2,5% Cu—0,5% Mg—14% Si), а потім перемішувалися в тривимірному міксері впродовж 45 хвилин. Потім порошки пресувалися та спікалися в атмосфері арґону при 640°C впродовж 4 годин. Одержані блоки зварювалися вольфрамовим зваренням в атмосфері інертного газу при 25 В, 197 А та потоці інертного газу у 14 л/хв. в атмосфері технічно чистого арґону. Було виконано макро- та мікродослідження деяких механічних властивостей зварної зони. їх результати показали, що, хоча виявилася велика кількість частинок зі зниженою густиною, ці композитні матеріяли можуть бути успішно зварені методою вольфрамового зварювання в атмосфері інертного газу.